2020
DOI: 10.1242/jeb.219238
|View full text |Cite
|
Sign up to set email alerts
|

Lipid content influences division of labour in a clonal ant

Abstract: The fat body, a major metabolic hub in insects, is involved in many functions, e.g. energy storage, nutrient sensing and immune response. In social insects, fat appears to play an additional role in division of labour between egg layers and workers, which specialize in nonreproductive tasks inside and outside their nest. For instance, reproductives are more resistant to starvation, and changes in fat content have been associated with the transition from inside to outside work or reproductive activities. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 76 publications
3
8
0
Order By: Relevance
“…The costs of intranidal tasks might be lower in P. punctata than in bees, e.g., brood care activities are probably more limited. We have also shown that P. punctata foragers can revert to nursing, egg laying, and regain fat content (Bernadou et al 2015(Bernadou et al , 2020. This suggests that workers are more flexible (Bernadou et al 2015(Bernadou et al , 2020 and that preforaging senescence can be reverted and is limited in comparison to honey bee workers.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…The costs of intranidal tasks might be lower in P. punctata than in bees, e.g., brood care activities are probably more limited. We have also shown that P. punctata foragers can revert to nursing, egg laying, and regain fat content (Bernadou et al 2015(Bernadou et al , 2020. This suggests that workers are more flexible (Bernadou et al 2015(Bernadou et al , 2020 and that preforaging senescence can be reverted and is limited in comparison to honey bee workers.…”
Section: Discussionmentioning
confidence: 55%
“…We have also shown that P. punctata foragers can revert to nursing, egg laying, and regain fat content (Bernadou et al 2015(Bernadou et al , 2020. This suggests that workers are more flexible (Bernadou et al 2015(Bernadou et al , 2020 and that preforaging senescence can be reverted and is limited in comparison to honey bee workers. For example, reverted nurses in the honey bee do not rebuild their lipid stores (Toth and Robinson 2005).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Among them, subcutaneous fat is the major component in the subcutaneous layer and is mainly composed of adipocytes. Traditionally, subcutaneous fat plays a major role in energy reserve, thermoregulation, and relief of the pressure from outside of the human body [1,2]. In addition, recent studies identified that the fat layer plays an additive function such as antimicrobial actions [3].…”
Section: Introductionmentioning
confidence: 99%
“…For individuals that do not reproduce, the onset of foraging often amounts to a death sentence. Leaving a natural nest to forage for food is certainly associated with a tremendous increase in external mortality, but foragers age rapidly also in the relatively safe environment of flight cages or laboratory nests [56,57]. While it is presently debated whether the residual life expectancy affects the start of foraging or vice versa (e.g.…”
Section: Effect Of Mating Reproductive Status and Taskmentioning
confidence: 99%